PEMBERDAYAAN MASYARAKAT MELALUI PENGEMBANGAN DESA SENTRA KOPI REMPAH - Widya Kusumaningsih; Ernawati Saptaningrum; Maria Ulfah; Khalimah Khalimah4 (Abdimas Altruis: Jurnal Pengabdian kepada Masyarakat, 2018)
This empowerment is a dedication to the people of Mlatiharjo Village, Patean District, Kendal Regency as a form of the Partner Village Development Program. This empowerment aims to a) provide solutions to the problems of the community in the form of the abundant spice coffee garden with a distinctive aroma of herbs with a holistic approach to multi-disciplinary research; b) empowering typical spices of coffee beans to become spice coffee powder with high selling value; c) provide the potential strengthening of the Mlatiharjo Village community through the application of research results in the form of making various spices; and d) forming a guided village as the Aneka Aroma Spice Coffee Sentra Village as one of the science-techno-park models of Semarang PGRI University. The method in implementing the Village Partner Development Program is by collaborating between three parties to resolve partner problems, namely Semarang PGRI University, Dikti's DRPM and Kendal District Government. The results of empowerment activities are processing coffee spices to become high-value coffee grounds, granting coffee processing equipment, P-IRT permits for coffee powder products produced, business licenses in the form of coffee shops and coffee cafes in the area and outside Kendal City, articles scientific and scientific publications. Conclusions of empowerment activities carried out in Mlatiharjo Village were successful, without any constraints and it was hoped that processing of spice coffee beans could become Mlatiharjo Village as a Spice Coffee Sentra Village and improve the economy of the Mlatiharjo Village community.